2012
DOI: 10.1159/000338495
|View full text |Cite
|
Sign up to set email alerts
|

Lycorine, a Candidate for the Control of Period Length in Mammalian Cells

Abstract: Plants of the Amaryllidaceae family have been used as therapeutic agents against CNS related maladies such as Alzheimer′s disease. The known primary alkaloid constituents have significant biological activity. We identified the Lycoris alkaloids lycorine and lycoricidinol from Amaryllidaceae using a real-time reporter gene assay system based on NIH3T3 cells. These alkaloids have a wide spectrum of pharmacological actions and dose-dependently lengthen the circadian period. When cells that had been incubated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
(57 reference statements)
1
22
0
Order By: Relevance
“…Lee et al recently reported that BMAL1 overexpression elongates the circadian period by ∼30 min (25). We also confirmed using real-time reporter gene assays that knockdown and overexpression of the Bmal1 gene result in the short- and long-period phenotype, respectively (24). Both camptothecin and Top1 siRNA enhanced Bmal1 transcription in both NIH3T3-derived and sarcoma 180-derived cell lines (Figure 3A and B) and the Top1 mutant expressed more Bmal1 (Figure 3C), suggesting that a decrease in Top1 activity enhances Bmal1 expression.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Lee et al recently reported that BMAL1 overexpression elongates the circadian period by ∼30 min (25). We also confirmed using real-time reporter gene assays that knockdown and overexpression of the Bmal1 gene result in the short- and long-period phenotype, respectively (24). Both camptothecin and Top1 siRNA enhanced Bmal1 transcription in both NIH3T3-derived and sarcoma 180-derived cell lines (Figure 3A and B) and the Top1 mutant expressed more Bmal1 (Figure 3C), suggesting that a decrease in Top1 activity enhances Bmal1 expression.…”
Section: Discussionsupporting
confidence: 69%
“…These results indicate that the downregulation of Top1 gene expression extends the circadian period of the Bmal1 gene. We (24) and others (25) have recently reported that the amount of Bmal1 expression is related to circadian rhythms. Here, we evaluated the relationship between levels of Bmal1 and Top1 gene expression.…”
Section: Resultsmentioning
confidence: 85%
“…Among these alkaloids, lycorine is the first active alkaloid of Amaryllidaceae family plants to be isolated from the plant Narcissus pseudonarcissus in 1877 [6], and has been extensively studied in its chemical molecule structures and biological functions (Figure 1). Lycorine possesses multiple pharmacological effects, including anti-tumor [712], anti-angiogenesis and tumor cell-mediated vasculogenic mimicry [11,12], anti-virus [1318], anti-bacteria [1921], antiinflammation [2225], inhibition of acetylcholinesterase (AChE) [2631], suppression of ascorbic acid biosynthesis [3235], anti-malaria [3639], control of period length [40], and exercise of choleretic effect [41]. More interestingly, lycorine has very low toxicity to normal cells and normal bodies at an effective dose.…”
Section: Introductionmentioning
confidence: 99%
“…Lycoris radiata (LR) belongs to the amaryllidaceae, which is a highly valuable Chinese traditional medicine and ornamental plant . Many kinds of alkaloids are present in LR, such as galanthamine (GA) and lycorine (LY) .…”
Section: Introductionmentioning
confidence: 99%
“…The LY could be used for antiphlogosis and analgesia , liver protection , mammalian cell cycle control, antiviral , antibiosis , as well as medicine for malaria and cancer . It could also be used for the synthesis of RNA and proteins , suppressing the growth of cells and the activity of the acetylcholine . There are many determination methods for GA and LY, such as UV‐visible spectrometry , chemiluminescence , fluorescence spectrometry , spectrophotometry , chromatography with MS , radioimmunoassay and so on.…”
Section: Introductionmentioning
confidence: 99%